EFFECT OF INTRAOPERATIVE MITOMYCIN-C APPLICATION IN OUTCOME OF EXTERNAL DACRYOCYSTORHINOSTOMY - Jawad, Mohammad; Ali, Zulfiqar; Tariq, Sumbal; Qayum, Iftikhar; Aftab, Hamad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Patients develop postoperative fibrosis at the site of operation after dacryocystorhinostomy (DCR) which results in impairment of the osteum patency. This quasi-experimental study was undertaken to determine the role of intraoperative Mitomycin C (MMC) application in maintaining postoperative patency of the osteum. Methodology: The present study was conducted at the Eye department of Ayub Medical College, Abbottabad on patients in whom routine DCR was indicated. Subjects were divided into mitomycin C (Test) and non mitomycin C (Control) groups. In test group, Mitomycin C was applied to the anastomosed flaps and osteotomy site for 30 minutes. Postoperative patients were followed for up to 6 months and outcome of patency was documented. Results: A total of 73 patients were included, divided into test (30) and control (43) groups. An overall success rate of 86.3% was obtained for patent ostia; this was based on 96.67% success in test group compared to 79.1% in the control group (p=0.031). Conclusion: Intraoperative application of Mitomycin-C significantly improves the success rate in external dacryocystorhinostomy.